2016
DOI: 10.1037/cdp0000097
|View full text |Cite
|
Sign up to set email alerts
|

Familism and Latino adolescent depressive symptoms: The role of maternal warmth and support and school support.

Abstract: Objectives: This study examined the relationship between familism and depressive symptoms across relational contexts in adolescence, and whether maternal warmth and support, and school support moderated the relationship between familism and depressive symptoms.Method: A total of 180 Latino adolescents (53% female) in 7th through 10th grades (average age = 14 years) participated in this cross-sectional study. The adolescents lived in an emerging Latino community in a rural area in the U.S. South. Most of the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 47 publications
1
20
1
Order By: Relevance
“…Rural Latino adolescents have family and school members as their primary social networks (García et al 2011;Tummala-Narra 2015), which can be protective or risk factors to their mental health. In fact, familism, or a strong connection to the family, is a recurrent theme throughout the literature (Baumann, Kuhlberg & Zayas 2010;García et al 2011;Campos, Ullman, Aguilera & Dunkel-Schetter, 2014;Tummala-Narra 2015;Cupito, Stein, Gonzalez, & Supple 2016). In many instances, the adolescents heavily relied on family support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rural Latino adolescents have family and school members as their primary social networks (García et al 2011;Tummala-Narra 2015), which can be protective or risk factors to their mental health. In fact, familism, or a strong connection to the family, is a recurrent theme throughout the literature (Baumann, Kuhlberg & Zayas 2010;García et al 2011;Campos, Ullman, Aguilera & Dunkel-Schetter, 2014;Tummala-Narra 2015;Cupito, Stein, Gonzalez, & Supple 2016). In many instances, the adolescents heavily relied on family support.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that Latino adolescents report a higher level of familism when compared to other immigrant populations (Campos et al, 2014). Positive familism and family relations contribute to a decreased risk for depressive symptoms (Campos et al, 2014;Cupito et al, 2016). The positive effects of familism in Latino adolescents, particularly relates to the relationships with their mothers (Baumann et al, 2010;Stacciarini et.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…This may be particularly true for the younger (relative to older) adolescent mothers who are more likely to be experiencing normative increases in depressive symptoms as a function of the transition through early and middle adolescence (Zeiders et al, 2013). To date, evidence suggesting the benefits of strong familism values for reducing youth depressive and internalizing symptoms comes primarily from studies of Mexican-origin youth in community- and school-based settings (Berkel et al, 2010; Burrow-Sanchez, Ortiz-Jensen, Corrales, & Meyers, 2015; Cupito, Stein, Gonzalez, & Supple, 2016; Zeiders et al, 2013). In a longitudinal study of Mexican-origin youth from early adolescence to young adulthood, for example, Zeiders et al (2013) showed that within-person fluctuations in familism values were related to depressive symptoms, such that on occasions when youth reported higher familism values than their own cross-time average, they also reported fewer depressive symptoms.…”
Section: Familism Values Family Relationship Dynamics and Adolescenmentioning
confidence: 99%